Radiological Anatomy Daily Lab Slides for Medical Gross Anatomy Courses - Andrew Phillips; Courtney Lawhn Heath; David Binder; Mylene Remo; Alexander Soneru; Michael King; Jeremy Wortman; Eric Barker; Kelly Ledbetter; William Uffmann; Christopher Straus (Association of American Medical Colleges, 2013)
Abstract This resource contains six PowerPoint presentations corresponding to the six major human body regions with labeled radiological anatomy structures and answer explanations designed for use by teaching assistants for small group instruction in a medical gross anatomy course. The slides and selected structures are designed to correspond with the structures being dissected or reviewed each day in a cadaver lab. They emphasize the spatial relationships structures have with one another that can often be appreciated differently in imaging compared to gross observation. Instruction time is approximately 10-15 minutes. These presentations and their variations have been in use successfully for four years at our institution by second and fourth year medical student teaching assistants daily as part of the gross anatomy course. This program has been successfully implemented the last four years of our gross anatomy course and is now an integral component of the course. A randomized controlled trial we conducted during the first year of implementation showed no statistically significant difference between students who received instruction that directly correlated radiological and gross structures vs students who received the radiological and gross structure instruction separately. Nonetheless we believe a direct correlation approach bears logic and may be helpful.